Whether it should be a legally enforceable duty to disclose one’s HIV status to a sexual partner : critical analysis of article 14(1)(e) of the African Women’s Protocol - Vahard, Patrice Ernest (University of Pretoria, 2008)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2008.